Characteristics of mismatched eplets affecting de novo donor-specific antibody production and antibody-mediated rejection after kidney transplantation - Mei-He Li; Gu-Xiang Zhou; Ping Lan; Yi-Xuan Li; Xuan Zhang; Pei-Dan Kuang; Ying Zhang; Ying Wang; Min-Yue Zhang; Xiao-Ming Ding; Wu-Jun Xue; Jin Zheng (BMC Nephrology)
Abstract De novo donor-specific antibody (dnDSA) generation is the most important marker of antibody-mediated rejection (AMR). However, not all dnDSAs induce AMR. The effects of mismatched eplets on dnDSA production and the occurrence AMR remain controversial. We analyzed 64 cases of dnDSA positive kidney transplantation that occurred between 2017 and 2021 at our center to reveal the relationships between mismatched eplet and dnDSA generation and the characteristics of antibody-specific and AMR associated mismatched eplets. Among the 64 dnDSA positive cases, 114 dnDSA were produced. Both the average production time and medium fluorescence index (MFI) value of human leukocyte antigen (HLA) II dnDSA were higher than those of HLA I (time, p = 0.024; MFI, p = 0.032). More HLA II dnDSAs were generated in the AMR group (p < 0.001). The frequency of HLA II dnDSAs was higher in cases of longer antibody generation time, higher MFI, and AMR( p < 0.05). The differences in the numbers of mismatched HLA I and II eplets were statistically significant between the rejection and no rejection groups (p = 0.030). dnDSA-specific and AMR associated mismatched eplets were strongly correlated (p < 0.0001). The dominant mismatched eplets included 41 T, 163R, 25Q, 78 V, 47QL and 55PP. dnDSA-specific eplets accounted for majority of the total mismatched eplets of donors and recipients. The amino acids with increased proportions of dnDSA-specific eplets were mainly non-polarity amino acids (p < 0.0001). AMR-associated mismatched eplets accounted for majority of the dnDSA-specific mismatched eplets. Arginine, histidine, glutamine, glutamate, lysine and asparagine levels increased significantly in the rejection group compared with the no rejection group (p < 0.001). The amino acids with increased proportions of AMR-associated mismatched eplets were all polar (p < 0.0001) and mainly positively charged (p < 0.0001). The polarity and charge of amino acids in mismatched eplets may be the key factors affecting the occurrence of AMR after kidney transplantation.